Women on the Institutional Circuit: A 9-Year Qualitative Study. (January 2019) - Sered, Susan Starr; Norton-Hawk, Maureen
Using a mixed-method approach of interviews and ethnographic observations, the authors followed a cohort of women postincarceration in Massachusetts for a period of 9 years. The women repeatedly cycled through health care and other institutions, yet very few moved into stable housing, jobs, and family situations. Nearly all continue to suffer multiple physical and mental health challenges despite high levels of access to health care. This article is intended to provide those who work in correctional institutions a broader view of the lives of justice-involved women outside of those institutions. In light of the short sentences and frequent breaks in continuity of care experienced by these women, the authors call for expansion of the roles of community health center providers inside jails and prisons.